PERAN UNI EROPA DALAM UPAYA MEMERANGI PEROMPAK SOMALIA DI TELUK ADEN PADA TAHUN 2008-2012 - Shaver, I Putu; Sushanti, Sukma; Prameswari, A.A.Ayu Intan (DIKSHI (DISKUSI ILMIAH KOMUNITAS HUBUNGAN INTERNASIONAL); Vol 1 No 03 (2015), 2015)
ABSTRAK The Somalian Pirates issue in Gulf of Aden has become a global issue which invites security concerns from countries to international organizations. Gulf of Aden is an important international trade routes. Thus, such disruption upon the trade route would jeopardize international trades and invite strong reactions among parties suffered from loss due to the piracy. Several European Union member countries harmed by this issues, then, demand European Union to address the issue and proactively involve in any measure necessary to solve the problem. In 8 th December 2008, European Union finally launched its first military operation to fulfill its role in combating the pirates. The Operation is called European Union Naval Force Atalanta (EU NAVFOR). This research is using qualitative method and several concepts in International Relations study such as non-traditional security, piracy, international organization, and roles concept. Keywords : Somalian Pirates, Gulf of Aden, European Union, EU NAVFOR Atalanta